Temperature-dependent electroplasticity in the Invar 36 alloy - Hongrui Dong; He Zhou; Yong Li; Xiaoqiang Li; Shiteng Zhao; Xiaochun Liu; Yaxin Wang (Journal of Materials Research and Technology, 2024)
Electroplasticity of the Invar 36 alloy is investigated based on comparisions between warm and electrically-assisted (EA) uniaxial tensions experiments at different temperatures (100–600 °C) and corresponding microstructural characterizations. Under warm deformation (WD), the flow stress decreases with the increase in temperature, which is directly attributed to dynamic recovery and dynamic recrystallization. With the introduction of high electric current during deformation, it shows a temperature-dependent electroplasticity phenomenon. No difference could be observed between WD and EA samples below a critical temperature of 500 °C, above which, an obvious softening behavior takes place in EA samples. This transition in softening respective to deformation temperature clearly demonstrated that it correlates with the intrinsic current-induced dislocation annihilation and recovery rather than the traditional theory of the Joule heating effect. Our findings shed more light on the utilization of EA softening effect on the development of novel forming routines, especially for materials with limited deformability.